Penggunaan PhET Simulations sebagai Laboratorium Virtual untuk Meningkatkan Keterampilan Memecahkan Masalah Mahasiswa - Ratna Azizah Mashami; Ahmadi; Yeti Kurniasih; Yusran Khery (Jurnal Penelitian Pendidikan IPA, 2023)
In the Radiochemistry course so far there have been no experimental activities because there are no laboratory facilities. Â However, with the use of technology, students can now easily access a wealth of educational resources online. This research aims to determine the effect of using the PhET Simulations as a virtual laboratory on students' problem solving skills. This research used mixed methods that combines quantitative and qualitative research. A quasi-experiment was carried out using a one group pretest-posttest design then continued with in-depth interviews. The instruments used in this research consisted of written tests to collect data on problem solving skills, questionnaires to collect student response, and interview guides to collect data on the problem solving process. Data in the form of problem solving skills were analyzed statistically using the SPSS 22.0 program while data obtained through questionnaires and interviews were analyzed descriptively. The results of the hypothesis test using Wilcoxon signed rank test show a significant value of 0.001, which means that PhET simulations as a virtual laboratory improve studentsâ€™ problem solving skills. Students are divided into high-medium-low groups based on problem solving ability and the majority of students are in the medium-ability group. Students responded positively to PhET Simulations as a virtual laboratory. In addition, interview transcripts provide an overview of how students think when solving chemistry problems.